I broke it down as follows
Y'' -3y^2 =0
Substituting I get v dv/dy = 3y^2
Separating variables, I get v dv =3y^2dy
Integrating I get 1/2v^2 +c = y^3 +c
Solving for v, I get v = (2y^3-2c)^1/2 which back substituting, = dy/dx
From here, it is a blur!! Initial conditions are y(0) =2, y'(0) =4
Can anybody help me from here?
Recently Asked Questions
- I need this answer to be at least 3 complete sentences. I will need to cite my assignment using cited scholarly articles or textbooks, so please include where
- Phillis and Trey are married and file a joint tax return. For 2018, they have $4,800 of nonbusiness capital gains, $2,300 of nonbusiness capital losses, $500
- Please refer to the attachment to answer this question. This question was created from Mid term practice fin 408 second.